2014
DOI: 10.5751/es-06787-190327
|View full text |Cite
|
Sign up to set email alerts
|

Campus sustainability and natural area stewardship: student involvement in adaptive comanagement

Abstract: ABSTRACT. University campus sustainability initiatives have proliferated over the last decade. We contend that such initiatives benefit from applying conceptual frameworks to help understand and guide their activities and from a focus on campus open space and natural areas management. Informed by an adaptive comanagement framework encompassing social learning, social capital, and shared action, we used semistructured interviews to examine student participation in the immediate response and longer-term policy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…This replicates findings from research on campus gardens and natural areas which shows that such sustainability initiatives can unite campus stakeholders (Duram and Williams, 2015;Krasny and Delia, 2014). Our survey showed that the relationships between teachers and students is enhanced because of the "great teaching opportunities" provided by gardens.…”
Section: Social Connectionssupporting
confidence: 70%
“…This replicates findings from research on campus gardens and natural areas which shows that such sustainability initiatives can unite campus stakeholders (Duram and Williams, 2015;Krasny and Delia, 2014). Our survey showed that the relationships between teachers and students is enhanced because of the "great teaching opportunities" provided by gardens.…”
Section: Social Connectionssupporting
confidence: 70%
“…Following educational lessons and deliberative dialogue among students and staff, the workshop culminated in students designing customized clothes patches, which could simultaneously be used to mend clothing and allow students to share educational messages with a broader audience (Jones & Podpadec, 2023). Other examples in the academic literature include educators standing in solidarity with youth voices to start local vegetable gardens in vacant city lots (Schusler et al, 2009) and collaborating with students to sustainably steward natural areas on a university campus (Krasny & Delia, 2014).…”
Section: Solidarity To Amplify Youth Voicesmentioning
confidence: 99%
“…Furthermore, SE facilitators range from academics and environmental consultants to agricultural extension specialists and government employees, each operating from varied methodologies with often equally varied results. Stakeholder engagement in natural resource management runs the spectrum from very large multinational and multiyear projects (see Partidário et al 2008, Kidd andMcGowan 2013) to local, tightly focused projects (see Knapp et al 2014, Krasny andDelia 2014) that span vast geographic, political, and cultural scales. In sum, stakeholder engagement initiatives occur across a very diverse range of project scopes and scales, can include a broad range of stakeholders, and are carried out by a diverse set of managers, facilitators, experts, and nonexperts-experienced and inexperienced alike.…”
Section: Defining Stakeholder Engagementmentioning
confidence: 99%